Analisis Idiomatis dan Filosofis Terhadap Frasa Amnos Tou Theou dalam Injil Yohanes 1:29 - Agus Prasetyo; Daniel Lindung Adiatma (Sekolah Tinggi Teologi Kalimantan, 2023)
Reconciliation theology in soteriological doctrine is often understood conceptually, which fails to provide a deeper theological significance to Christian beliefs. As a result, Christians comprehend the concept of atonement through Christ but lack a profound understanding that can be applied to their religious behavior. The phrase